Above‐ to belowground carbon allocation in peatlands shifts with plant functional type and temperature. Issue 1 (21st November 2021) - Zeh, Lilli; Schmidt‐Cotta, Claudia; Limpens, Juul; Bragazza, Luca; Kalbitz, Karsten
Abstract: Background: Northern peatlands have accumulated vast amounts of carbon (C) as peat. Warming temperatures may affect peatland C stores by increasing microbial decomposition of ancient peat through enhanced input of labile root exudates by expansion of vascular plants, thereby accelerating atmospheric warming. Aims: We set out to explore how much freshly assimilated C is allocated belowground by vascular plants, and if the above‐ to belowground allocation is affected by temperature and plant functional types. Methods: We traced the C allocation pathways of two dominant plant functional types (i.e., sedges and shrubs) in two peatlands under different temperature regimes by combining selective plant removal in mixed sedge‐shrub vegetation and in situ 13 C pulse‐labelling. Aboveground to belowground C allocation as well as the C turnover were assessed by quantifying 13 C in plant leaves and soil respiration and by measuring δ 13 C in dissolved organic C. A depth‐resolved quantification of 13 C in the peat soil gave additional insight into belowground C allocation patterns. Results: Temperature did not affect the rate at which 13 C was assimilated into shoots, but higher temperature decreased the fraction of assimilated C that was allocated belowground by vascular plants. Sedges assimilated CO2 faster into their shoot biomass (faster depletion in 13 C in shoots) and allocated more of the assimilated 13 C belowground than shrubs. Conversely, sedges retained this belowground allocated C better than shrubs, leading to lower 13 C in soil respiration measured under sedges. Conclusions: Climate induced vascular plant expansion will increase input of fresh assimilates into the peat substantially, even though part of this effect will be offset by reduced above‐ to belowground allocation rates. If shrub density increases relative to sedges, fresh assimilates are more likely to be respired than translocated to roots where they could reach and, potentially mobilize, ancient C stored in deeper peat layers.